Characterization of the ATP4 ion pump in Toxoplasma gondii - Lehane, A; Dennis, A; Bray, K; Li, D; Rajendran, E; McCoy, J; McArthur, H; Winterberg, M; Rahimi, F; Tonkin, C; Kirk, K; Van Dooren, G (American Society for Biochemistry and Molecular Biology, 2019)
The Plasmodium falciparum ATPase PfATP4 is the target of a diverse range of antimalarial compounds, including the clinical drug candidate cipargamin. PfATP4 was originally annotated as a Ca2+ transporter, but recent evidence suggests that it is a Na+ efflux pump, extruding Na+ in exchange for H+. Here we demonstrate that ATP4 proteins belong to a clade of P-type ATPases that are restricted to apicomplexans and their closest relatives. We employed a variety of genetic and physiological approaches to investigate the ATP4 protein of the apicomplexan Toxoplasma gondii, TgATP4. We show that TgATP4 is a plasma membrane protein. Knockdown of TgATP4 had no effect on resting pH or Ca2+, but rendered parasites unable to regulate their cytosolic Na+ concentration ([Na+]cyt). PfATP4 inhibitors caused an increase in [Na+]cyt and a cytosolic alkalinization in wild type, but not in TgATP4-knockdown, parasites. Parasites in which TgATP4 was knocked down or disrupted exhibited a growth defect, attributable to a reduced viability of extracellular parasites. Parasites in which TgATP4 had been disrupted showed reduced virulence in mice. These results provide evidence for ATP4 proteins playing a key, conserved role in Na+ regulation in apicomplexan parasites.